On-farm rice diversity and farmers' preferences for varietal attributes in Ayeyarwady Delta, Myanmar. Issue 4 (3rd July 2020) - Thant, Aye Aye; Teutscherova, Nikola; Vazquez, Eduardo; Kalousova, Marie; Phyo, Aung; Singh, Rakesh Kumar; Lojka, Bohdan
ABSTRACT: Myanmar falls within the center of the genetic diversity of many economically important crops, including wild and cultivated rice ( Oryza sativa L.). However, the majority of the genetic resources of Myanmar, particularly local varieties, and their distribution remain poorly understood. The present study was conducted to investigate the on-farm varietal diversity and the determinants of farmers' variety choices in the Ayeyarwady delta in southern Myanmar, specifically for rainfed rice cultivation. Data from 150 randomly selected households, distributed across five townships, were collected through a semi-structured questionnaire. Households were located in three agro-ecological zones based on the predominant water type (fresh, brackish, and saline). The on-farm diversity appeared to be relatively high according to the number of varieties grown by the farmers. In total, 39 varieties were identified within the survey area. Only 34% of the interviewed farmers grew high-yielding varieties (HYVs) at least on a fraction of their land and the likelihood of adoption of HYVs decreased with length of farming experience, education, and soil fertility, but increased with total area sown under rice according to binomial regression model. From a policy perspective for the high adoption of HYVs, the establishment of a product profile for developing new rice varieties should give priority to farmers' desired attributes and the vital features, such as resistance to environmental stresses or/and preferred qualitative rice properties, rather than solely considering increased yield.